The Influence of Communication Teamwork and Work Discipline on Employee Performance at PT. Pratomo Putra Teknik Palopo - Rika Rika; Indra Kusdarianto; Samsinar (Jurnal Economic Resource, 2023)
This study aims to determine the effect of communication teamwork and work discipline on employee performance at PT Pratomo Putra Teknik Palopo. This research method is a quantitative one, and data collection involved distributing questionnaires directly to employees of PT Pratomo Putra Teknik Palopo, with the subject of this research involving 40 respondents. In this study, using a Likert scale with a questionnaire statement, respondents answered "strongly disagree" to "strongly agree" to each question on each indicator. The data analysis method used is multiple linear regression analysis. The results of the partially tested research show that communication and teamwork have a positive and significant effect on employee performance at PT Pratomo Putra Teknik Palopo. Meanwhile, work discipline has a positive and significant impact on employee performance, and employee performance has a positive and significant impact on work discipline and communication teamwork at PT Pratomo Putra Teknik Palopo.